Upaya Peningkatan Hasil Belajar Kognitif dan Kemampuan Berpikir Kreatif Siswa Melalui Media E-Book Berekstensi Epub - Mudrika Umami; Haning Hasbiyati; Imam Bukhori Muslim (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This study aims to improve students’ learning outcomes and creative thinking skills through e-book media with EPUB extensions. The type of research used is classroom action research (CAR) with cycle prosedures. Based on the results of the study, students’ learning outcomes in the cycle I was 70%, then it had increased to 73,25% in cycle II. Students’ creative thinking skills was 57% in the cycle I and it had decreased to 55% in cycle II. The aspect of creative thinking ability in cycle I was 50% and it had increase to 53,5% in cycle II. Thus, it can be inferred that the results of cognitive learning and creative thingking skills of class IX students of SMK Hidayatul Mubtadiin can be improved by the use of e-book media with EPUB ekstensions. Keywords : learning outcomes, creative thinking skills, e-book, EPUB.